Social prescribing for suicide prevention: a proposed model for Australia - Dash, Sarah; McNamara, Stella; de Courten, Maximilian; Calder, Rosemary (Frontiers in Public Health, 2025)
Suicidality is a devastating and burdensome experience that can be a result of complex psychological, biological and social factors. Social prescribing could be well suited to address the diverse non-clinical needs of people experiencing suicidality. International and Australian evidence indicates social prescribing provides an effective and acceptable approach. To address suicide risk and rates in the Australian community, community-based approaches that are visible, readily accessible and that address complex social, practical or non-medical needs are needed. We propose a social prescribing model for suicide prevention that could be implemented in Australia either as a specific purpose service or within existing social prescribing trials, with relevant modifications tailored to suicide prevention. Drawing upon evidence from the literature and a panel of social prescribing experts, we make practical recommendations for implementing a social prescribing model for suicide prevention in Australia, and discuss some of the system-wide requirements to support access and scaling up of these models.